The Insufficiency of High School Completion Rates to Redress Educational Inequities among Indigenous Students - Louie, Dustin; Gereluk, Dianne (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2021)
A continued gap exists in student achievement between Indigenous and non- Indigenous students in the British Columbia school system. This article analyzes the balance of success and failure of the Accountability Framework, a provincial program designed to increase graduation rates in the province. In order to understand the successes and failures of this initiative, we draw upon the principles of John Rawls to consider the implications of rising graduation rates of those occupying the lowest standard of living in society. One of the primary findings is the necessity of policy makers and educational leaders to refrain from considering data regarding Indigenous student success in isolation and instead consider the shifts in disparity compared to non-Indigenous learners. Shifting the level of analysis from the school system to the overall well-being of a population unearths serious concerns regarding indicators of success within school systems. We contend that the initiative to solely draw upon high school completion rates as an indicator of success is misleading and further exacerbates existing problems of marginalization of Indigenous people in education.